A Broadband Single-Feed Circularly Polarized Patch Antenna with Wide Beamwidth - Changhong Zhang; Junping Geng; Bin Zhou; Xianling Liang; Ronghong Jin (International Journal of Antennas and Propagation)
A broadband single-feed circularly polarized patch antenna with wide beamwidth is presented. The patch is coupled to four asymmetric cross slots via a microstrip ring with eight matching segments underneath the ground plane, traversing through the arms of the cross slots in a serial manner. And a coupling slice instead of a resistive load is used as matching load of the microstrip ring for higher gain. Furthermore, a metal side wall surrounding the antenna is used to improve the isolation between adjacent elements in an array. Through optimizing the four asymmetric cross slots and eight matching segments, excellent performances are achieved by the proposed antenna, especially for the broadband and wide beamwidth. Measurement results show that the antenna has −10 dB reflection coefficient bandwidth of 29.7%, 3-dB axial-ratio bandwidth of 21.6%, and beamwidth of more than 90°. It can be considered as a good candidate for the element of arrays.